Strategi Pembelajaran Seni Tari Melalui Model Kooperatif Di Sekolah Dasar - Aziz Murof Suharyanto; Sutrisna Wibawa; Heri Maria Zulfiati (Universitas Sarjanawiyata Tamansiswa, 2023)
There are still many problems faced in learning dance in schools, even though the contribution of dance art education is very significant for building the character of students and the character of the nation. Dance art education can provide space for optimal multi-intelligence development of students. Related to this problem, research was conducted with the aim of describing the process and results of increasing interest in learning the art of dance. The learning model used in this study is a cooperative learning model using audio-visual media in the form of dance videos and LCDs as a means to support practical activities in dancing. The problem in this study is how the process of learning dance through the application of cooperative models using audio-visual media in fifth grade students of SD Negeri Dalem Kotagede. This research is a classroom action research using descriptive research methods and qualitative approaches. This research uses two cycles, where in the first cycle and the second cycle is the application of the cooperative learning model. The results of this study showed an increase in student interest from pre-cycle to cycle II. The conclusion of this study is that learning dance through a cooperative model with audio-visual media indicators of student interest such as indicators of attention, enjoyment, and interest in participating in dance learning has increased.